ARDUINO BASED VEHICLE COLLISION DETECTION USING CAN PROTOCOL - Shanmathi, S.; Kamalanathan, Prof.C. (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
Vehicle accidents are one of the leading causes of fatalities. Because of not getting help on time, poor emergency facilities, people lose their lives. This project deals with the optimum solution to this drawback. This paper presents the development and implementation of a digital driving system for a semiautonomous vehicle to improve the driver-vehicle interface. It uses an ARDUINO based data acquisition system that uses ADC to bring all control data from analog to digital format and visualize through LCD. The communication module used in this project is embedded networking by CAN which has efficient data transfer. In order to reduce point to point wiring harness in vehicle automation, CAN is suggested as a means for data communication within the vehicle environment. The benefits of CAN bus based network over traditional point to point schemes will offer increased flexibility and expandability for future technology insertions